Design, Synthesis and Bioassays of 3‐Substituted‐3‐Hydroxyoxindoles for Cholinesterase Inhibition. Issue 13 (19th August 2016) - Totobenazara, Jane; Bacalhau, Patrícia; Juan, Amor A. San; Marques, Carolina S.; Fernandes, Luís; Goth, Albertino; Caldeira, A. Teresa; Martins, Rosário; Burke, Anthony J.
Abstract: Based on the positive bioassay results of the known oxindole hit compound rac ‐1‐benzyl‐3‐hydroxy‐3‐phenylindolin‐2‐one which showed significant inhibition of butyrylcholinesterase (BuChE) (IC50 =7.41 μM), a library of 31 analogues of 3‐substituted‐3‐hydroxyoxindoles was synthesized and screened for both acetylcholinesterase (AChE) and BuChE activity. Our bioassays revealed that some of the new compounds exhibited moderate inhibition of eel AChE ( Ee AChE) and very good inhibition of equine serum BuChE ( Eq BuChE) with a best IC50 of 1.02 μM. On the basis of these results, the lead compound 1‐((1‐benzylpiperidin‐4‐yl)methyl)‐3‐hydroxy‐3‐phenylindolin‐2‐one was designed, which was shown to interact well with the enzymes active sites by molecular docking, was synthesized and upon bioassay gave an IC50 of 6.61 μM for BuChE. Interestingly, when we separated rac ‐benzyl‐3‐hydroxy‐3‐phenylindolin‐2‐one into the individual enantiomers ( R )‐ and ( S )‐benzyl‐3‐hydroxy‐3‐phenylindolin‐2‐one it was the latter enantiomer that gave the best IC50 of 6.19 μM for BuChE. Abstract : N ‐Benzyl‐2‐hydroxyoxindole1 was identified as a hit for BuChE inhibition. A series of analogues were designed, synthetized (using efficient catalytic methods) and assayed against both AChE and BuChE, most were selective for BuChE. Compound28 gave the best inhibition of BuChE (1 μM). Lead optimization based on previous knowledge, including molecular docking, resulted in compound31, designed to have favorable drug properties.